Antiviral therapy for hepatitis B virus during second pregnancies. Issue 3 (11th December 2017) - Wakano, Yasuhiro; Sugiura, Tokio; Endo, Takeshi; Ito, Koichi; Suzuki, Mitsuyoshi; Tajiri, Hitoshi; Tanaka, Yasuhito; Saitoh, Shinji
Abstract: Mother‐to‐child transmission of the hepatitis B virus (HBV) is a major concern for infected mothers, especially after their first child has become an HBV carrier despite immunoprophylaxis. Eight mothers whose first child had become an HBV carrier despite immunoprophylaxis were referred for antiviral therapy during the subsequent pregnancy. All pregnant women were seropositive for both the hepatitis B surface antigen and hepatitis B e antigen. In the treatment group (three receiving lamivudine and two receiving tenofovir), mother‐to‐child transmission of the HBV was successfully prevented in all infants (5/5). On the other hand, two of three infants became HBV carriers in the untreated group. There were no significant adverse effects in either mothers or infants. Antiviral therapy using lamivudine and tenofovir during the second pregnancy successfully prevented mother‐to‐child transmission of the HBV for high‐risk mothers.